Rigid Body Relativistic Motion

Classical Mechanics Level pending

Consider a rigid rod of length L L and rest mass M M uniformly distributed uniformly along the length of the rod. One end of the rod is hinged at the origin and the rod rotates about the Z-axis at a constant angular speed ω \omega . Compute the relativistic kinetic energy of the rod. The result comes out to be:

T = M c 2 ( π A B C ) \mathcal{T} = Mc^2\left(\frac{\pi^A}{B}-C\right)

Where T \mathcal{T} denotes the kinetic energy of the rod. Enter your answer as A + B + C \boxed{A+B+C} , where A A and B B and C C are positive integers. Take:

ω = c 2 L \omega = \frac{c}{2L}

Where c c is the speed of light.

Hint: Start with the expression for the relativistic kinetic energy for a point mass.

Bonus: Try to derive the classical result using the final expression that you obtain.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Steven Chase
Apr 26, 2020

Some preliminaries:

d m = M d r L v = r ω dm = \frac{M \, dr}{L} \\ v = r \omega

Relativistic KE for a segment of length d r dr :

d T = d m c 2 ( 1 1 r 2 ω 2 c 2 1 ) = M d r L c 2 ( 1 1 r 2 ω 2 c 2 1 ) d \mathcal{T} = dm \, c^2 \, \Big( \frac{1}{\sqrt{1 - \frac{r^2 \omega^2}{c^2}}} - 1 \Big) = \frac{M \, dr}{L} \, c^2 \, \Big( \frac{1}{\sqrt{1 - \frac{r^2 \omega^2}{c^2}}} - 1 \Big)

Integrating from r = 0 r = 0 to r = L r = L results in:

T = M c 2 L [ c w s i n 1 ( ω L c ) L ] \mathcal{T} = \frac{M c^2}{L} \Big[\frac{c}{w} sin^{-1} \Big(\frac{\omega L }{c} \Big) - L \Big]

Plugging in ω = c 2 L \omega = \frac{c}{2L} in the relativistic case:

T = M c 2 L [ 2 L s i n 1 ( 1 2 ) L ] = M c 2 [ 2 π 6 1 ] = M c 2 [ π 3 1 ] \mathcal{T} = \frac{M c^2}{L} \Big[2 L sin^{-1} \Big(\frac{1 }{2} \Big) - L \Big] = M c^2 \Big[2 \frac{\pi}{6} - 1\Big] = M c^2 \Big[ \frac{\pi}{3} - 1\Big]

Now, for the low-energy case, we can use an approximation for arcsine, assuming that the argument is small.

s i n 1 x x + x 3 6 sin^{-1} x \approx x + \frac{x^3}{6}

Plugging in:

T = M c 2 L [ c w ( ω L c + ω 3 L 3 6 c 3 ) L ] = M c 2 L ( ω 2 L 3 6 c 2 ) = M ( ω 2 L 2 6 ) = 1 2 M L 2 3 ω 2 = 1 2 I r o d ω 2 \mathcal{T} = \frac{M c^2}{L} \Big[\frac{c}{w} \Big(\frac{\omega L }{c} + \frac{\omega^3 L^3 }{6 c^3} \Big) - L \Big] \\ = \frac{M c^2}{L} \Big( \frac{\omega^2 L^3 }{6 c^2} \Big) \\ = M \Big( \frac{\omega^2 L^2 }{6} \Big) = \frac{1}{2} \frac{M L^2}{3} \omega^2 = \frac{1}{2} I_{rod} \, \omega^2

Thus, in the low-energy limit, the relativistic expression boils down to the ordinary kinetic energy expression for a rod rotating about one end.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...